A new index to assess the situation of subgroups, with an application to public transport disadvantage in US metropolitan areas. (December 2022) - Pritchard, John P.; Zanchetta, Anna; Martens, Karel
Abstract: The evaluation of how particular segments of society fare is a common concern in many policy and academic realms, including transportation. The Target group Position Index (TPI) is introduced to assess the relative situation of a target group compared to a larger population. It uses two distinct population-specific benchmarks to determine the relative position of the subgroup: a theoretical worst-case and a theoretical best-case situation. An application of the index to transport is also presented, using 49 of the largest US metropolitan regions as case studies. Job accessibility by public transport is assessed for two population subgroups especially likely to benefit from public transport: adults without a car and adults living in poverty. It is found that the car-less population is comparatively better served by public transport than the poor population. Additionally, regions with a higher TPI score for car-less populations also tend to have public transport systems that better serve their population living in poverty. These results highlight that the proposed index allows for easy comparison across regions, despite large differences in the scale of the variable of interest (accessibility by public transport), the total population, and the size of the target groups (car-less or adults in poverty). Highlights: The TPI is introduced to analyze target groups within a larger population. The TPI may be used for equity analysis within a prioritarian perspective of justice. In the US, the car-less pop. is better served by public transport than the poor pop.